2011
DOI: 10.1111/j.1468-2494.2011.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic agents and herbs in topical application for acne treatment

Abstract: SynopsisAcne vulgaris suppresses an individual's self-confidence by causing distress with regard to physical appearance, which affects a significant number of individuals during puberty and is delineated by adolescence. Several treatments have been introduced to decrease the aesthetic and psychological problems caused by acne. The topical application of therapeutic agents has been found to be more feasible than hormonal treatment and laser therapy. The ingredients in topical acne treatments, particularly herbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 125 publications
2
61
0
1
Order By: Relevance
“…28 and linolenic acid 19.22 including palmitic acid 8.56 and stearic acid 10.56 7 . The rubber seed oil was claimed safe as evaluated in animal models 5,7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 and linolenic acid 19.22 including palmitic acid 8.56 and stearic acid 10.56 7 . The rubber seed oil was claimed safe as evaluated in animal models 5,7 .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, they are respected as the efficient actives for acne treatment 28 . Palmitic acid has several physiological functions, including suppression of cholesterol 29 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the novel antiacne compound identified belongs to the piperidide family, which are known to be antimicrobial, antiviral, larvicidal, insecticidal, diuretic, pungent, analgesic, cannabimimetic and antioxidant (Rios, 2012). Some of the plant sources that are known to have anti-acne effect are Aloe vera (Grace et al, 2008), Azadirachta indica, Curcuma longa, Hemidesmus incidus, Gossypium barbadense (Kanlayavattanakul and Lourith 2011), essential oils of Eucalyptus radiate and Melaleuca alternifolia (Stevensen, 1998). But none of these studies have successfully identified a compound that could treat the array of acne causes such as free radicals, reducing inflammation, killing acne causing bacteria and also reduce pigmentation after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…42 The herbs were found to effectively reduce inflammatory acne lesions through mechanisms related to sebaceous glands, Propionibacterium acnes, and reactive oxygen species (ROS). 43 The herbal topical medication (QoolSkin) reduced the Psoriasis Area and Severity Index (PASI) by 32.0% and the Beer-Sheva Psoriasis Severity Score (BPSS) by 37.8% in patients with chronic plaque psoriasis. 44 Poison oak and related hypersensitivity dermatitides had been successfully treated with herbal medicines Grindelia spp.…”
Section: Herbal Medications Benefit For Dermatological Manifestationsmentioning
confidence: 99%